Multiparty testing preorders - De Nicola, Rocco (2023)
Variants of the must testing approach have been successfully applied in service oriented computing for analysing the compliance between (contracts exposed by) clients and servers or, more generally, between two peers. It has however been argued that multiparty scenarios call for more permissive notions of compliance because partners usually do not have full coordination capabilities. We propose two new testing preorders, which are obtained by restricting the set of potential observers. For the first preorder, called uncoordinated, we allow only sets of parallel observers that use different parts of the interface of a given service and have no possibility of intercommunication. For the second preorder, that we call individualistic, we instead rely on parallel observers that perceive as silent all the actions that are not in the interface of interest. We have that the uncoordinated preorder is coarser than the classical must testing preorder and finer than the individualistic one. We also provide a characterisation in terms of decorated traces for both preorders: the uncoordinated preorder is defined in terms of must-sets and Mazurkiewicz traces while the individualistic one is described in terms of classes of filtered traces that only contain designated visible actions and must-sets.